Composite positive electrode material and preparation method and application thereof

By incorporating the first oxide electrolyte crystal into the skeleton of the lithium-rich manganese-based positive electrode material and covering the second oxide electrolyte layer, the problem of degradation of cyclic performance caused by the instability of the material is solved, and higher structural stability and electrochemical performance are achieved.

CN119890257AInactive Publication Date: 2025-04-25CHONGQING TALENT NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411993168.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have unstable structure during the circulation process, resulting in a degradation of cycling performance.

Method used

By incorporating the first oxide electrolyte crystal into the skeleton of the positive electrode material and covering the second oxide electrolyte layer on the surface, a composite positive electrode material is formed.

Benefits of technology

It improves the structural stability and cyclic properties of the material, reduces the side reaction between the material and the electrolyte, and enhances the electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890257A_ABST
    Figure CN119890257A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy, and particularly relates to a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material provided by the invention comprises a main phase and a doped phase coexisting with the main phase, the main phase comprises a positive electrode material crystal, and the doped phase is a first oxide electrolyte crystal doped into a main phase skeleton. The oxide electrolyte is doped into the framework of the positive electrode material, a semi-coherent interface is formed between the oxide electrolyte and the positive electrode material, the stability of the oxide electrolyte is higher, a pinning effect can be formed, conversion from a layered structure of the positive electrode material to a spinel structure can be inhibited, escape of active oxygen is controlled, and the structural stability of the material is improved; the cycle performance is improved; furthermore, the surface of the positive electrode material is coated with an oxide solid electrolyte coating layer, so that side reactions on the surface of the material can be reduced, the surface stability of the material is improved, and the electrochemical performance of the material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of new energy technology, and specifically relates to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] The current strict requirements of lithium-ion batteries for energy density have led to the development of cathode materials that are moving towards high energy density such as high nickel, cobalt-free, and lithium-rich. 2 MnO 3 (1-x)LiTMO 2 ,TM=Ni,Co,Mn) material is regarded as one of the most promising positive electrode materials in the field of next-generation lithium-ion batteries due to its ultra-high specific capacity, high voltage characteristics and significant cost advantages.

[0003] Lithium-rich manganese-based materials use relatively cheap manganese as their main component and have a low content of precious metals. Compared with common lithium cobalt oxide and nickel-cobalt-manganese ternary positive electrode materials, lithium-rich manganese-based materials reduce costs and improve safety. In addition, lithium-rich manganese-based materials have a wide voltage window (2.0-4.8V) and better cycle stability under conventional pressure than other commercialized positive electrode materials. When matched with a silicon-carbon negative electrode, the energy density of its battery cell is expected to exceed 400Wh / kg. At the same time, as a low-nickel and high-manganese positive electrode material, its low watt-hour cost is comparable to that of lithium iron phosphate. However, the irreversible release of oxygen that occurs in lithium-rich manganese-based materials during the cycle will accelerate the irreversible evolution of the material's crystal structure, ultimately leading to the structural collapse of the material, thereby affecting its cycle performance. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of the lithium-rich manganese-based positive electrode materials in the prior art, such as unstable structure and influence on cycle performance, so as to provide a composite positive electrode material and its preparation method and application.

[0005] To this end, this application provides the following technical solutions:

[0006] According to one aspect of the present application, a composite positive electrode material is provided, comprising: a main phase and a doped phase coexisting with the main phase, wherein the main phase comprises positive electrode material crystals, and the doped phase is a first oxide electrolyte crystal doped into the main phase skeleton.

[0007] In some optional embodiments, the oxide electrolyte crystals include at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, and lithium lanthanum titanate.

[0008] In some optional embodiments, it further includes a coating layer located on the surface of the main phase, and the coating layer includes a second oxide electrolyte;

[0009] Optionally, based on the total mass of the composite positive electrode material, the mass percentage of the first oxide electrolyte crystals is 0.1%-5%;

[0010] Further optionally, the coating layer has a thickness of 10-100 nm.

[0011] In some optional embodiments, the positive electrode material crystals include: at least one of lithium-rich manganese-based materials, nickel-cobalt-manganese ternary materials, lithium cobalt oxide materials, and nickel-cobalt-aluminum oxide lithium materials;

[0012] Optionally, the positive electrode material crystal is a lithium-rich manganese-based material, and its chemical composition satisfies the following general formula: xLi 2 MnO 3 (1-x)LiTMO 2 , where TM = Ni, Co or Mn, and the value range of x is 0.3-0.7.

[0013] According to another aspect of the present application, a method for preparing the above-mentioned composite positive electrode material is provided, comprising the following steps:

[0014] S1, mixing a metal source solution and a first oxide electrolyte precursor salt solution, performing a precipitation reaction, and obtaining a precursor;

[0015] Wherein, the metal element in the metal source solution includes at least one of Ni, Co, Mn and Al;

[0016] S2, mixing the precursor with a lithium source, and sintering to obtain the composite positive electrode material.

[0017] In some optional embodiments, in S1, after the precipitation reaction, the step of adding a second oxide electrolyte precursor salt solution to continue the precipitation reaction is also included.

[0018] In some optional embodiments, in S1, the molar ratio of the metal element in the first oxide electrolyte precursor salt, the metal element in the second oxide electrolyte precursor salt, and the metal element in the metal source solution is 1:1-5:94-98.

[0019] In some optional embodiments, in S1, the pH of the precipitation reaction is 8-9;

[0020] And / or, in S2, the molar ratio of the metal element in the metal source solution to the lithium element in the lithium source is 1:1.05-1:1.50;

[0021] And / or, in S2, the sintering temperature is 800-1000°C, and the sintering time is 6-18h; optionally, the sintering temperature is 850-950°C.

[0022] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned composite positive electrode material or the composite positive electrode material prepared by the above-mentioned preparation method.

[0023] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned lithium-ion battery.

[0024] The technical solution of this application has the following advantages:

[0025] The composite positive electrode material provided by the present application comprises: a main phase and a doped phase coexisting with the main phase, wherein the main phase comprises positive electrode material crystals, and the doped phase is a first oxide electrolyte crystal doped into the main phase skeleton. The present application dopes the oxide electrolyte into the skeleton of the positive electrode material to form a semi-coherent interface with the positive electrode material. Since the oxide electrolyte has a higher stability, a pinning effect can be formed, which can inhibit the transformation of the positive electrode material layered structure to the spinel structure, control the escape of active oxygen, improve the material structure stability, and improve the cycle performance.

[0026] The composite positive electrode material provided in the present application also includes a coating layer located on the surface of the main phase, and the coating layer includes a second oxide electrolyte. In the present application, a layer of oxide electrolyte coating layer is coated on the surface of the composite positive electrode material to reduce the side reaction between the material surface and the electrolyte and improve the surface stability of the material. The electrochemical performance of the material is further improved through the combined effect of the two aspects.

[0027] The preparation method of the composite positive electrode material provided in the present application comprises the following steps: S1, mixing a metal source solution and a first oxide electrolyte precursor salt solution, performing a precipitation reaction, and obtaining a precursor; wherein the metal element in the metal source solution comprises at least one of Ni, Co, Mn, and Al; S2, mixing the precursor with a lithium source, sintering, and obtaining the composite positive electrode material. The preparation process provided in the present application can incorporate a highly stable oxide solid electrolyte crystal phase into the bulk phase lattice of the positive electrode material, and the preparation process is simple, the yield is high, and it is very suitable for mass production and convenient for popularization and application.

[0028] The lithium-ion battery provided in the present application comprises the composite positive electrode material or the composite positive electrode material prepared by the above-mentioned preparation method. The lithium-ion battery has higher cycle stability because it uses a composite positive electrode material with higher stability.

[0029] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 Schematic diagram of the structure of the composite positive electrode material provided in the embodiment of the present application;

[0032] Figure 2 It is the equivalent circuit diagram used in the impedance value test of this application;

[0033] Reference numerals:

[0034] 1. Positive electrode material crystal; 2. First oxide electrolyte crystal; 3. Coating layer. DETAILED DESCRIPTION

[0035] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0037] According to one aspect of the present application, a composite positive electrode material is provided, comprising: a main phase and a doped phase coexisting with the main phase, wherein the main phase comprises positive electrode material crystals, and the doped phase is a first oxide electrolyte crystal doped into the main phase skeleton.

[0038] In the present application, an oxide electrolyte is incorporated into the skeleton of the positive electrode material crystal, and a semi-coherent interface or a semi-coherent structure is formed between the positive electrode material crystal and the oxide electrolyte crystal. Since the oxide electrolyte has a higher stability, a pinning effect can be formed, which can inhibit the transformation of the layered structure of the positive electrode material to the spinel structure, control the escape of active oxygen, improve the stability of the material structure, and improve the cycle performance.

[0039] It is understood by those skilled in the art that the term "semi-coherent interface" refers to an interface where misfit dislocations exist on the interface between adjacent grains in a composite crystal. If the distance between two adjacent grain surfaces is greatly different, the atoms on the interface cannot completely correspond one to one, and some crystal planes do not have a corresponding relationship, thus forming a semi-coherent interface.

[0040] In some optional embodiments, the oxide electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium aluminum titanium phosphate (LATP), and lithium lanthanum titanate (LLTO), preferably lithium lanthanum zirconium oxide (LLZO).

[0041] In some optional embodiments, a coating layer is further included, which is located on the surface of the main phase, and the coating layer includes a second oxide electrolyte.

[0042] In the present application, coating a layer of oxide solid electrolyte coating on the surface of the composite positive electrode material can reduce the side reaction between the material surface and the electrolyte and improve the surface stability of the material. The electrochemical performance of the composite positive electrode material is further improved through the combined effect of the two aspects.

[0043] It will be understood by those skilled in the art that the composition of the first oxide electrolyte crystal and the second oxide electrolyte may be the same or different.

[0044] In some optional embodiments, the mass percentage of the first oxide electrolyte crystals is 0.1%-5% based on the total mass of the composite positive electrode material. As an example, the mass percentage of the first oxide electrolyte crystals can be 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or within the range of any of the above values. By limiting the content of the first oxide electrolyte in the composite positive electrode material, the present application can ensure that it has an effective stabilizing effect on the positive electrode material crystals without affecting the performance of the positive electrode material crystal capacity.

[0045] Optionally, the coating layer has a thickness of 10-100 nm. As an example, the coating layer has a thickness of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or within a range consisting of any of the above values.

[0046] The present application can effectively protect the positive electrode material by setting the coating layer, reduce the occurrence of side reactions with the electrolyte, and improve the lithium ion conductivity of the composite positive electrode material. The coating layer thickness is limited to the above reasonable range to avoid the coating layer being too thick to affect the capacity of the positive electrode material.

[0047] In the present application, the thickness of the coating layer can be tested by methods known in the art and herein. As an example, a transmission electron microscope TEM can be used for measurement.

[0048] In some optional embodiments, the positive electrode material crystals include: at least one of lithium-rich manganese-based materials, nickel-cobalt-manganese ternary materials, lithium cobalt oxide materials, and nickel-cobalt-aluminum oxide lithium materials;

[0049] Optionally, the positive electrode material crystal is a lithium-rich manganese-based material, and its chemical composition satisfies the following general formula: xLi 2 MnO 3 (1-x)LiTMO 2 , wherein TM = Ni, Co or Mn, and the value range of x is 0.3-0.7; further optionally, the general chemical formula is: xLi 2 MnO 3 ·(1-x)LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O 2 .

[0050] According to another aspect of the present application, a method for preparing a composite positive electrode material is provided, comprising the following steps:

[0051] S1, mixing a metal source solution and a first oxide electrolyte precursor salt solution, performing a precipitation reaction, and obtaining a precursor;

[0052] Wherein, the metal element in the metal source solution includes at least one of Ni, Co, Mn and Al;

[0053] S2, mixing the precursor with a lithium source, and sintering to obtain the composite positive electrode material.

[0054] The preparation process provided in the present application can incorporate highly stable oxide electrolyte crystals into the bulk lattice of the positive electrode material crystal, and the preparation process is simple, the yield is high, and it is very suitable for mass production, and it is convenient for promotion and application. Specifically, in step S1, the metal element in the metal source solution and the metal element in the first oxide electrolyte precursor salt solution are coprecipitated to obtain a doped precursor, and the metal elements in the metal source solution in the precursor are arranged in a layered structure, and the metal elements in the first oxide electrolyte precursor salt solution replace part of the metal elements in the metal source solution and are inserted into the above-mentioned layered structure; in step S2, during the roasting process after the precursor is mixed with the lithium source, the metal elements in the first oxide electrolyte precursor salt solution grow in situ with Li and O elements to form the first oxide electrolyte crystal, and the metal elements in the metal source solution grow in situ with Li and O elements to form the positive electrode material crystal, and the two crystals grow in situ together, which can realize the in-situ introduction of the first oxide electrolyte crystal in the skeleton of the positive electrode material crystal, and form a semi-coherent interface or semi-coherent structure between the positive electrode material crystal and the oxide electrolyte crystal.

[0055] In some optional embodiments, in step S1, after the precipitation reaction, the step further includes adding a second oxide electrolyte precursor salt solution to continue the precipitation reaction.

[0056] In the present application, the metal source solution may be a soluble salt solution containing the corresponding metal element, for example, a sulfate, nitrate, etc. containing the corresponding metal element; the first oxide electrolyte precursor salt solution and the second oxide electrolyte precursor salt solution refer to soluble salt solutions used to prepare oxide electrolytes, which are selected according to the type of oxide electrolyte. For example, when the oxide electrolyte is lithium lanthanum zirconium oxide (LLZO), the corresponding precursor salt solution is a soluble salt solution containing La elements and Zr elements, including but not limited to sulfates, nitrates, etc. During the solution mixing process, each soluble metal salt can be prepared into a solution separately, and then mixed, and the concentration of each soluble metal salt solution can be 0.5-5mol / L. As an example, the concentration of each soluble metal salt solution can be 0.5mol / L, 1mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, or within the range of any of the above values. In some optional embodiments, the composition of the first oxide electrolyte precursor salt solution and the second oxide electrolyte precursor salt solution may be the same or different, and preferably the two compositions are the same.

[0057] In the present application, the lithium source is conventional in the field, including but not limited to at least one of lithium carbonate, lithium hydroxide monohydrate, etc.

[0058] In some optional embodiments, in step S1, the molar ratio of the metal element in the first oxide electrolyte precursor salt, the metal element in the second oxide electrolyte precursor salt, and the total amount of the metal element in the metal source solution is 1:1-5:94-98. As an example, the molar ratio of the metal elements among the three can be 1:1:98, 1:2:97, 1:3:96, 1:4:95, 1:5:94, or within the range of any of the above values.

[0059] In the present application, by limiting the total amount of metal elements in the first oxide electrolyte precursor salt, the second oxide electrolyte precursor salt and the metal elements in the metal source solution within the above-mentioned range, it is possible to achieve a balance between the stability, conductivity and capacity of the positive electrode material. This is because the main role of the oxide electrolyte material is to support the structure of the positive electrode material and improve the surface stability of the material, and it does not provide capacity itself. Therefore, too much will lead to a decrease in the capacity of the positive electrode material.

[0060] In some optional embodiments, in step S1, the pH of the precipitation reaction is 8-9; as an example, the pH of the precipitation reaction can be 8, 8.2, 8.5, 8.7, 9, or within the range of any of the above values. Specifically, the pH of the reaction system can be adjusted by ammonia water or the like. In the present application, the precipitation reaction is a precipitation reaction using carbonate ions, and as an example, a soluble carbonate, such as sodium carbonate, is added to the mixed system.

[0061] And / or, in step S2, the molar ratio of the total amount of metal elements in the metal source solution to the lithium element in the lithium source is 1:1.05 to 1:1.50. As an example, the molar ratio of the total amount of metal elements in the metal source solution to the lithium element in the lithium source is 1:1.05, 1:1.10, 1:1.15, 1:1.26, 1:1.30, 1:1.40, 1:1.45, 1:1.50, or within the range of any of the above values.

[0062] In some optional embodiments, in step S2, the sintering temperature is 800-1000°C. As an example, the sintering temperature can be 800°C, 850°C, 880°C, 900°C, 930°C, 970°C, 1000°C, or within the range of any of the above values; the sintering time is 3-24h; as an example, the sintering time can be 3h, 5h, 8h, 10h, 12h, 16h, 18h, 20h, 24h, or within the range of any of the above values. In the present application, the appropriate sintering temperature and sintering time can be adjusted according to the different types of positive electrode materials and oxide electrolytes.

[0063] Optionally, the sintering temperature is 850-950°C; as an example, the sintering temperature may be 850°C, 880°C, 900°C, 920°C, 950°C, or within a range consisting of any of the above values.

[0064] In some optional embodiments, in step S2, a pre-firing step is further included before sintering, and optionally, the pre-firing temperature is 400-600°C, and the pre-firing time is 3-9h. As an example, the pre-firing temperature can be 400°C, 420°C, 450°C, 480°C, 500°C, 530°C, 550°C, 570°C, 600°C, or within the range of any of the above values; the pre-firing time can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, or within the range of any of the above values.

[0065] The preparation method of the lithium-rich manganese-based positive electrode material is specifically described below when the oxide electrolyte is LLZO, comprising the following steps:

[0066] (1) NiSO4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O and La (NO 3 ) 3 、Zr(NO 3 ) 4 Deionized water was used to prepare 0.5-5 mol / L solutions, and then La(NO 3 ) 3 and Zr(NO 3 ) 4 Solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring tank in a certain proportion and mixed, and a certain proportion of Na 2 CO 3 solution (0.5-5mol / L) and ammonia water (0.5-2mol / L), keep the solution pH in the stirred tank at 8-9, and continue stirring. After a period of time, stop adding Ni, Co, and Mn solutions, and continue to add a certain amount of La(NO 3 ) 3 、Zr(NO 3 ) 4 The obtained solution is then centrifuged and dried to obtain a precipitate, namely, a lithium-rich manganese-based precursor.

[0067] (2) The prepared lithium-rich manganese-based precursor is mixed evenly with the lithium salt, zirconium oxide balls are added into the ball mill of the mixer in the ratio of large ball: medium ball: small ball = 1:1:1, and the precursor obtained in the above step (1) is added, and then the lithium salt is added in a molar ratio of the sum of the metal elements in the metal source solution to the lithium element in the lithium source of 1:1.05 to 1:1.50, and then mixed.

[0068] (3) After the mixing in step (2) is completed, the material is placed in a muffle furnace and sintered at a certain temperature to obtain a lithium-rich manganese-based positive electrode material (i.e., a composite positive electrode material) in situ doped and coated with an oxide solid electrolyte LLZO.

[0069] Furthermore, in the step (2), the mixing speed is 100 to 500 rpm / min, the mixing time is 3 to 24 hours, and the ball-to-material ratio is 1:1 to 5:1.

[0070] Furthermore, in step (1), the drying temperature is 80 to 120° C., and the drying time is 6 to 24 hours.

[0071] The preparation method of the composite positive electrode material provided in the present application introduces a highly lithium-conductive and highly stable oxide solid electrolyte material in situ into the lattice and surface of the lithium-rich manganese-based material, which not only improves the stability of the structure and surface of the lithium-rich manganese-based material, but also improves the lithium ion conductivity of the material. In addition, the preparation process adopted in the present application is simple and has a high yield, which is very suitable for mass production.

[0072] According to another aspect of the present application, a lithium ion battery is provided, comprising the composite positive electrode material or the composite positive electrode material prepared by the above preparation method. The lithium ion battery has higher cycle stability due to the use of a composite positive electrode material with higher stability.

[0073] In the present application, the lithium-ion battery may include, in addition to the above-mentioned composite positive electrode material, a negative electrode sheet, a separator or an electrolyte, etc. These compositions and preparation methods are conventional in the field and are not specifically limited here.

[0074] As an example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector. The material (positive electrode active material includes the composite positive electrode material provided by the above aspects of the present application) of the positive electrode sheet used in the lithium ion secondary battery of the present application, the composition and the manufacturing method thereof may include any technology disclosed in the prior art.

[0075] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector. The material (as an example, including but not limited to negative electrode materials such as graphite, silicon carbon, and metallic lithium), composition, and manufacturing method of the negative electrode sheet used in the lithium-ion secondary battery of the present application may include any technology disclosed in the prior art.

[0076] The material (as examples, including but not limited to PP, PE, composite separators with ceramic coatings, etc.) and shape of the separator used in the lithium-ion secondary battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.

[0077] The electrolyte used in the lithium-ion secondary battery of the present application (lithium salts thereof include but are not limited to LiPF 6 , LiFSi, etc.) may include any technology disclosed in the prior art.

[0078] According to another aspect of the present application, there is provided an electric device, comprising the above-mentioned lithium-ion battery. The advantages of the electric device and the above-mentioned lithium battery over the prior art are the same, which will not be described in detail here.

[0079] In the present application, the lithium-ion battery can be used as a power source for the electrical equipment, or as an energy storage unit for the electrical equipment. The electrical equipment can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0080] The present application is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present application in any way.

[0081] Example 1

[0082] This embodiment provides a composite positive electrode material, and its structural schematic diagram is as follows Figure 1 As shown, it includes positive electrode material crystals 1 and first oxide electrolyte crystals 2 distributed in the positive electrode material crystals 1; a coating layer 3 is arranged on at least a portion of the surface of the positive electrode material crystals 1, and the coating layer 3 includes a second oxide electrolyte.

[0083] The preparation method of the composite positive electrode material is as follows:

[0084] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O was prepared into 2 mol / L solution with deionized water and La(NO 3 ) 3 、Zr(NO 3 ) 4 Deionized water was used to prepare 0.2 mol / L solutions, and then the La(NO 3 ) 3 and Zr(NO 3 ) 4 Solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring kettle at the molar ratio of La:Zr:TM (TM = Ni, Co, Mn, where the molar ratio of Ni:Co:Mn = 3:3:14) = 0.6:0.4:97, and 2 mol / L Na 2 CO3 solution and 1 mol / L ammonia water, keep the pH of the solution in the stirred tank at 8.6, and continue stirring. Add for half an hour, stop adding the three solutions of Ni / Co / Mn, and continue to add a certain amount of La(NO 3 ) 3 、Zr(NO 3 ) 4 The solution was prepared so that the overall element molar ratio of the solution in the final stirred tank was La: Zr: TM = 1.8: 1.2: 97. The prepared solution was then centrifuged and dried to obtain a precipitate, i.e., a lithium-rich manganese-based precursor (Mn 0.7 Co 0.15 Ni 0.15 CO 3 ) x ·(La 6 Zr 4 (CO 3 ) 17 ) 1-x .

[0085] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.25:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-burning for 4h, then heat it to 950℃ at 2℃ / min for sintering for 12h. After that, the sintered material is crushed and sieved to obtain a composite positive electrode material with a particle size Dv50 of about 10μm; after testing, the thickness of the coating layer is about 32nm.

[0086] Example 2

[0087] This embodiment provides a composite positive electrode material, and its structural schematic diagram is as follows Figure 1 As shown, it includes positive electrode material crystals 1 and first oxide electrolyte crystals 2 distributed in the positive electrode material crystals 1; a coating layer 3 is arranged on at least a portion of the surface of the positive electrode material crystals 1, and the coating layer 3 includes a second oxide electrolyte.

[0088] The preparation method of the composite positive electrode material is as follows:

[0089] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O and La (NO 3 )3 、Zr(NO 3 ) 4 Deionized water was used to prepare a 2 mol / L solution, and then La(NO 3 ) 3 and Zr(NO 3 ) 4 Solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring kettle at the molar ratio of La:Zr:TM (TM = Ni, Co, Mn, where the molar ratio of Ni:Co:Mn = 3:3:14) = 0.6:0.4:98, and 2 mol / L Na 2 CO 3 solution and 1 mol / L ammonia water, keep the pH of the solution in the stirred tank at 8.6, and continue stirring. Add for half an hour, stop adding the Ni / Co / Mn solutions, and continue to add a certain amount of La(NO 3 ) 3 、Zr(NO 3 ) 4 The solution was prepared such that the overall element molar ratio of the solution in the final stirred tank was La:Zr:TM = 1.2:0.8:98. The prepared solution was then centrifuged and dried to obtain a precipitate, i.e., a lithium-rich manganese-based precursor (Mn 0.7 Co 0.15 Ni 0.15 CO 3 ) x ·(La 6 Zr 4 (CO 3 ) 17 ) 1-x .

[0090] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.25:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-burning for 4h, then heat it to 950℃ at 2℃ / min for sintering for 12h. After that, the sintered material is crushed and sieved to obtain a composite positive electrode material with a particle size Dv50 of about 10μm; after testing, the thickness of the coating layer is about 22nm.

[0091] Example 3

[0092] This embodiment provides a composite positive electrode material, and its structural schematic diagram is as follows Figure 1 As shown, it includes positive electrode material crystals 1 and first oxide electrolyte crystals 2 distributed in the positive electrode material crystals 1; a coating layer 3 is arranged on at least a portion of the surface of the positive electrode material crystals 1, and the coating layer 3 includes a second oxide electrolyte.

[0093] The preparation method of the composite positive electrode material is as follows:

[0094] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O and La (NO 3 ) 3 、Zr(NO 3 ) 4 Deionized water was used to prepare a 2 mol / L solution, and then La(NO 3 ) 3 and Zr(NO 3 ) 4 Solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring kettle at the molar ratio of La:Zr:TM (TM = Ni, Co, Mn, where the molar ratio of Ni:Co:Mn = 3:3:14) = 0.6:0.4:96, and 2 mol / L Na 2 CO 3 solution and 1 mol / L ammonia water, keep the pH of the solution in the stirred tank at 8.6, and continue stirring. Add for half an hour, stop adding the Ni / Co / Mn solutions, and continue to add a certain amount of La(NO 3 ) 3 、Zr(NO 3 ) 4 The solution was prepared such that the overall element molar ratio of the solution in the final stirred tank was La:Zr:TM=2.4:1.6:96. The prepared solution was then centrifuged and dried to obtain a precipitate, i.e., a lithium-rich manganese-based precursor (Mn 0.7 Co 0.15 Ni 0.15 CO 3 ) x ·(La 6 Zr 4 (CO3 ) 17 ) 1-x .

[0095] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.25:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-burning for 4h, then heat it to 950℃ at 2℃ / min for sintering for 12h. After that, the sintered material is crushed and sieved to obtain a composite positive electrode material with a particle size Dv50 of about 10μm; after testing, the thickness of the coating layer is about 39nm.

[0096] Example 4

[0097] This embodiment provides a composite positive electrode material. Compared with Embodiment 1, the only difference is that in step S1, the pH value of the solution in the stirring tank is maintained at 8; in step S2, the pre-burning temperature is 600° C. and the pre-burning time is 3 h.

[0098] Example 5

[0099] This embodiment provides a composite positive electrode material. Compared with Embodiment 1, the only difference is that in step S1, the pH value of the solution in the stirring tank is maintained at 9; in step S2, the pre-burning temperature is 400° C. and the pre-burning time is 9 hours.

[0100] Example 6

[0101] This embodiment provides a composite positive electrode material. Compared with Embodiment 1, the only difference is that in step S2, the sintering temperature is 1000° C. and the sintering time is 6 hours.

[0102] Example 7

[0103] This embodiment provides a composite positive electrode material. Compared with Embodiment 1, the only difference is that in step S2, the sintering temperature is 800° C. and the sintering time is 18 h.

[0104] Example 8

[0105] This embodiment provides a composite positive electrode material. Compared with Example 3, the only difference is that: in step S1, solutions containing La, Zr, and TM elements are added to the stirring tank at the same time, La:Zr:TM=1.2:0.8:96; after stopping the addition of the three solutions of Ni / Co / Mn, the overall element molar ratio of the solution in the stirring tank is finally made La:Zr:TM=2.4:1.6:96.

[0106] Example 9

[0107] This embodiment provides a composite positive electrode material, which is different from the embodiment 1 in that: in step S1, the molar ratio of Ni, Co, and Mn in TM is Ni:Co:Mn=3:4:13;

[0108] In S2, 100 g of lithium carbonate and lithium-rich manganese-based precursor mixture are weighed at a Li:TM molar ratio of 1.35:1.

[0109] Example 10

[0110] This embodiment provides a composite positive electrode material, which is different from Embodiment 1 only in that step S2 does not include a pre-firing step.

[0111] Embodiment 11

[0112] This embodiment provides a composite positive electrode material, and the specific preparation method is as follows:

[0113] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O and Al(NO 3 ) 3 NH 4 H 2 PO 4 , respectively, prepared with deionized water to make a 2 mol / L solution, n-butyl titanate (C 16 H 36 O 4 Ti) was prepared into a 2 mol / L solution with anhydrous ethanol. 16 H 36 O 4 Ti、Al(NO 3 ) 3 and NH 4 H 2 PO 4 Solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring kettle in the proportion of element molar ratio Ti:Al:P:TM (TM = Ni, Co, Mn, where the molar ratio Ni:Co:Mn = 3:3:14) = 0.34:0.06:0.6:98.5, and 2 mol / L Na 2 CO 3solution and 1 mol / L ammonia water, keep the pH of the solution in the stirring tank at 8.6, and continue stirring. Add for half an hour, stop adding the three solutions of Ni / Co / Mn, and continue to add a certain amount of C 16 H 36 O 4 Ti、Al(NO 3 ) 3 and NH 4 H 2 PO 4 The solution was prepared such that the overall element molar ratio of the solution in the final stirred tank was Ti:Al:P:TM=0.51:0.09:0.9:98.5. The prepared solution was then centrifuged and dried to obtain a precipitate, i.e., a lithium-rich manganese-based precursor (Mn 0.7 Co 0.15 Ni 0.15 CO 3 ) x ·(Al 0.3 Ti 1.7 (PO 4 ) 3 ) 1-x .

[0114] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.15:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-burning for 4h, then heat it to 950℃ at 2℃ / min for sintering for 12h. After that, the sintered material is crushed and sieved to obtain a composite positive electrode material with a particle size Dv50 of about 10μm; after testing, the thickness of the coating layer is about 4nm.

[0115] Example 12

[0116] This embodiment provides a composite positive electrode material, and the specific preparation method is as follows:

[0117] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O and La (NO 3 ) 3 Prepare 2 mol / L solution with deionized water, C 16 H 36 O 4Ti was prepared into a 2 mol / L solution with anhydrous ethanol. Then La(NO 3 ) 3 and C 16 H 36 O 4 Ti solution and NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added to the stirring kettle at the molar ratio of La:Ti:TM (TM = Ni, Co, Mn, where the molar ratio of Ni:Co:Mn = 3:3:14) = 0.56:1:96.8, and 2 mol / L Na 2 CO 3 solution and 1 mol / L ammonia water, keep the pH of the solution in the stirred tank at 8.6, and continue stirring. Add for half an hour, stop adding the Ni / Co / Mn solutions, and continue to add a certain amount of La(NO 3 ) 3 , C 16 H 36 O 4 The prepared solution was centrifuged and dried to obtain a precipitate, i.e., a lithium-rich manganese-based precursor (Mn 0.7 Co 0.15 Ni 0.15 CO 3 ) x ·(La 0.56 Ti 1.0 O 3 ) 1-x .

[0118] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.10:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-sintering for 4h, then heat it to 950℃ at 2℃ / min for sintering for 12h. After that, the sintered material is crushed and sieved to obtain a composite positive electrode material with a particle size Dv50 of about 10μm; after testing, the thickness of the coating layer is about 32nm.

[0119] Comparative Example 1

[0120] This comparative example provides a lithium-rich manganese-based positive electrode material. Compared with Example 1, the difference is that no oxide electrolyte is introduced. The specific preparation method is as follows:

[0121] S1, the raw material NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O were prepared into 2 mol / L solutions with deionized water, and then NiSO 4 ·H 2 O、MnSO 4 ·H 2 O. CoSO 4 ·H 2 O solution was added into the stirring kettle at the molar ratio of Ni:Co:Mn=3:3:14, and 2 mol / L Na 2 CO 3 The solution and 1 mol / L ammonia water were added to keep the pH of the solution in the stirred tank at 8.6 and stirred continuously. The addition of Ni / Co / Mn solutions was stopped after half an hour. The prepared solution was then centrifuged and dried to obtain a precipitate, i.e., the lithium-rich manganese-based precursor Mn 0.7 Co 0.15 Ni 0.15 CO 3 .

[0122] S2. Weigh 100g of lithium carbonate and lithium-rich manganese-based precursor mixture at a Li:TM molar ratio of 1.05:1. Mix large zirconium oxide balls (8mm in diameter), medium balls (5mm in diameter), and small balls (2mm in diameter) at a mass ratio of 1:1:1 to form mixed zirconium balls. Weigh 200g of mixed zirconium oxide balls at a ball-to-material mass ratio of about 2:1 and put them into an inclined barrel mixer for mixing for 12 hours. After the mixing is completed, put it into a sagger and put it into a muffle furnace. Heat it to 500℃ at 2℃ / min for pre-burning for 4 hours, then heat it to 950℃ at 2℃ / min for sintering for 12 hours. After that, the sintered material is crushed and sieved to obtain a lithium-rich manganese-based positive electrode material with a particle size of about 10μm.

[0123] Comparative Example 2

[0124] This comparative example provides a composite positive electrode material. Compared with Example 1, the difference is that no oxide electrolyte is introduced into the core, that is, La(NO 3 ) 3 、Zr(NO 3 ) 4 The specific operation steps are the same as step S1 of comparative example 1.

[0125] Comparative Example 3

[0126] This comparative example provides a composite positive electrode material, wherein the lithium-rich lithium manganese oxide (Li 1.2 (Mn 0.56 Co 0.12 Ni 0.12 ) 2 ) is mixed with LLZO, of which LLZO accounts for 6%.

[0127] Test Case

[0128] The composite positive electrode materials obtained in each embodiment and comparative example were respectively mixed with a conductive agent and a binder to form positive electrode sheets, and then mixed with a metal lithium sheet to form a CR2032 button battery for performance testing. The details are as follows:

[0129] <Pole production>

[0130] The composite positive electrode material, carbon black and polyvinylidene fluoride prepared in each embodiment and comparative example were weighed in a mass ratio of 90:5:5, and then an appropriate amount of N-methylpyrrolidone was added and mixed evenly into a slurry; the slurry was coated on an aluminum foil and dried at 80°C for 4 hours (the coating thickness was 150 μm, and the thickness after drying and compaction was 60 μm). The dried electrode was cut into The discs were rolled and dried in a vacuum oven at 80°C for 12 h.

[0131] <Button Battery Production>

[0132] The negative electrode is a metal lithium sheet, the diaphragm is a double-layer 12μm thick ceramic-coated polyethylene diaphragm, and the electrolyte is 1MLiPF 6 The solvent is a mixed solution of EC (ethylene carbonate) and DEC (diethyl carbonate), and the mass ratio of the two is 3:7. The assembly of the button is carried out in a glove box filled with argon protection. After the assembly, it is left to stand for 12 hours before the test begins.

[0133] (1) Impedance value:

[0134] The impedance value of the button cell made of the composite positive electrode material obtained in each embodiment and comparative example was measured by the AC impedance test method. Specifically, the button cell for testing was placed in the Chenhua electrochemical workstation CHI660E for AC impedance test at 3.7V after three cycles at 2.8V-4.6V@0.2C, with the frequency set to 0.1HZ~1MHZ and the voltage amplitude set to 5mV. In the equivalent circuit (such as Figure 2 As shown), R 1 represents the ohmic resistance of the liquid electrolyte, R 2 Represents the interface resistance, R 3 Represents the charge transfer resistance. Focus on R 2 and R 3The resistance calculated based on the equivalent circuit is shown in Table 1.

[0135] Table 1

[0136] Case <![CDATA[R 2 (Oh)]]> <![CDATA[R 3 (Oh)]]> Example 1 38.2 83.4 Example 2 37.3 82.1 Example 3 39.2 86.3 Example 4 46.9 107.6 Example 5 45.7 102.5 Example 6 39.5 90.2 Example 7 38.8 92.3 Example 8 39.3 85.5 Example 9 39.8 91.3 Example 10 40.7 95.6 Embodiment 11 43.2 98.8 Example 12 46.3 99.7 Comparative Example 1 66.8 152.2 Comparative Example 2 55.2 137.3 Comparative Example 3 50.3 106.8

[0137] It can be seen from the table that the impedance values ​​of Examples 1-12 are all smaller than those of Comparative Examples 1-2, especially R 2 and R 3 This is mainly because the oxide solid electrolyte is incorporated into the layered structure of the positive electrode material as a skeleton, inhibiting the transformation of the positive electrode material from a layered structure to a spinel structure. Therefore, its interface resistance and charge transfer resistance are both small, which improves the electrochemical performance of the positive electrode material, especially the lithium-rich manganese-based material.

[0138] (2) Cycle performance:

[0139] The button cells made of the composite positive electrode materials obtained in each embodiment and comparative example were subjected to a 25°C cycle performance test with a cycle rate of 1C / 1C and a voltage range of 2.0V-4.6V for charge and discharge. The capacity retention rate and voltage drop were calculated after 200 cycles. The voltage drop is the median voltage difference between two adjacent cycles. Here, the average value of the voltage difference after each cycle (the difference in average discharge voltage) is taken. The results are shown in Table 2.

[0140] Table 2

[0141]

[0142]

[0143] It can be seen from the table that the capacity retention rates of Examples 1-12 are all higher than those of Comparative Examples 1-2, and the voltage drop is also significantly improved. This is mainly because the oxide solid electrolyte is incorporated into the layered structure of the positive electrode material as a skeleton, which stabilizes its layered structure and inhibits the transformation of the positive electrode material from a layered structure to a spinel structure. Therefore, the voltage drop is reduced, and the cycle performance of the lithium-rich manganese-based material is improved.

[0144] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A composite positive electrode material, characterized in that: include: A main phase and a doped phase coexisting with the main phase, wherein the main phase includes positive electrode material crystals, and the doped phase is a first oxide electrolyte crystal doped into the main phase skeleton.

2. The composite positive electrode material according to claim 1, characterized in that The oxide electrolyte crystals include at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, and lithium lanthanum titanate.

3. The composite positive electrode material according to claim 1 or 2, characterized in that: Also includes a coating layer, located on the surface of the main phase, the coating layer includes a second oxide electrolyte; Optionally, based on the total mass of the composite positive electrode material, the mass percentage of the first oxide electrolyte crystals is 0.1%-5%; Further optionally, the coating layer has a thickness of 10-100 nm.

4. The composite positive electrode material according to claim 3, characterized in that: The positive electrode material crystals include: at least one of lithium-rich manganese-based materials, nickel-cobalt-manganese ternary materials, lithium cobalt oxide materials, and nickel-cobalt-aluminum oxide lithium materials; Optionally, the positive electrode material crystal is a lithium-rich manganese-based material, and its chemical composition satisfies the following general formula: xLi2MnO3·(1-x)LiTMO2, wherein TM=Ni, Co or Mn, and the value range of x is 0.3-0.

7.

5. A method for preparing the composite positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing a metal source solution and a first oxide electrolyte precursor salt solution, performing a precipitation reaction, and obtaining a precursor; Wherein, the metal element in the metal source solution includes at least one of Ni, Co, Mn and Al; S2, mixing the precursor with a lithium source, and sintering to obtain the composite positive electrode material.

6. The method for preparing a composite positive electrode material according to claim 5, characterized in that: In the above S1, after the precipitation reaction, the step of adding a second oxide electrolyte precursor salt solution to continue the precipitation reaction is also included.

7. The method for preparing a composite positive electrode material according to claim 6, characterized in that: In S1, the molar ratio of the metal element in the first oxide electrolyte precursor salt, the metal element in the second oxide electrolyte precursor salt and the metal element in the metal source solution is 1:1-5:94-98.

8. The method for preparing a composite positive electrode material according to claim 6, characterized in that: In S1, the pH of the precipitation reaction is 8-9; And / or, in S2, the molar ratio of the metal element in the metal source solution to the lithium element in the lithium source is 1:1.05-1:1.50; And / or, in S2, the sintering temperature is 800-1000° C. and the sintering time is 6-18 h; Optionally, the sintering temperature is 850-950°C.

9. A lithium ion battery, characterized in that: The invention comprises the composite positive electrode material according to any one of claims 1 to 4 or the composite positive electrode material prepared by the preparation method according to any one of claims 5 to 8.

10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Composite coated ternary precursor as well as preparation method and application thereof

    CN114242970A

  • Ternary single-crystal positive electrode material, preparation method, post-processing method and application

    CN115799473A